Molecular breeding of water lily: engineering cold stress tolerance into tropical water lily. Issue 1 (30th November 2018) - Yu, Cuiwei; Qiao, Guirong; Qiu, Wenmin; Yu, Dongbei; Zhou, Shirong; Shen, Yan; Yu, Guanchun; Jiang, Jing; Han, Xiaojiao; Liu, Mingying; Zhang, Liangsheng; Chen, Fei; et al.
Abstract: Water lilies (order Nymphaeales) are rich in both economic and cultural values. They grow into aquatic herbs, and are divided into two ecological types: tropical and hardy. Although tropical water lilies have more ornamental and medicinal values compared to the hardy water lily, the study and utilization of tropical water lilies in both landscaping and pharmaceutical use is greatly hindered due to their limited planting area. Tropical water lilies cannot survive the winter in areas beyond 24.3°N latitude. Here, the transgenic pipeline through the pollen-tube pathway was generated for water lily for the first time. To improve cold stress tolerance of tropical water lilies, a gene encoding choline oxidase ( CodA ) driven by a cold stress-inducible promoter was transformed into a tropical water lily through the pollen-tube transformation. Six independent transgenic lines were tested for survival rate during two winter seasons from 2015 to 2017 in Hangzhou (30.3°N latitude). PCR and southern blot detection revealed that the CodA gene had been integrated into the genome. Reverse transcription PCR showed that CodA gene was induced after cold stress treatment, and further quantitative real-time PCR revealed different expressions among six 4 lines and line 3 had the highest expression. Multiple physiological experiments showed that after cold stress treatment, both the conductivity and malondialdehyde (MDA) levels from transgenic plants were significantly lower than those of non-transgenic plants, whereas the content of betaine and the activity of superoxide dismutase, catalase, and peroxidase were higher than those from non-transgenic plants. These results suggest that expression of exogenous CodA gene significantly improved the cold stress tolerance of tropical water lilies through a wide range of physiological alterations. Our results currently expanded a six-latitude cultivating area of the tropical water lilies. These results not only illuminate the bright future for water lily breeding but will also facilitate the functional genomic studies. Genetics: The crop that came in from the cold: Pioneering work in the genetic modification of water lilies lays the foundation for engineering more robust strains of this agriculturally valuable crop. Tropical water lilies are used to manufacture products including tea, food and essential oils, but their cultivation is limited by sensitivity to cold. Researchers led by Fei Chen at Fujian Agriculture and Forestry University have developed a genetic engineering procedure for introducing favorable new traits into these plants, offering an efficient alternative to labor-intensive crossbreeding procedures. As an initial demonstration, the researchers engineered tropical water lilies with a gene that confers enhanced cold tolerance, allowing the plants to survive winter temperatures that would otherwise prove inhospitable. This process should accelerate development of lilies that grow in a more diverse range of climates, and enable more extensive genomic analysis of this crop.